2017
DOI: 10.1155/2017/7053959
|View full text |Cite
|
Sign up to set email alerts
|

TSH Variability of Patients Affected by Differentiated Thyroid Cancer Treated with Levothyroxine Liquid Solution or Tablet Form

Abstract: Background Recent guidelines from the American Thyroid Association (ATA) indicate that, in many patients affected by differentiated thyroid cancer (DTC), the serum TSH should be maintained between 0.1 and 0.5 mU/L. The purpose of this study was to evaluate the TSH variability of patients affected by DTC treated with liquid L-T4 formulation or in tablet form. Patients and Methods Patients were eligible if (a) they were submitted to a total thyroidectomy and 131I remnant ablation for DTC in our institution and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
2
16
0
2
Order By: Relevance
“…A significant increase in TSH levels (median) was observed in patients taking tablets, as compared to those taking liquid formulation. These data suggest that the use of L‐T4 liquid formulation, as compared to that of tablets, resulted in a significantly higher number of DTC patients maintaining TSH values in range for the American Thyroid Association (ATA) risk score, reducing TSH variability over the time .…”
Section: Discussionmentioning
confidence: 94%
“…A significant increase in TSH levels (median) was observed in patients taking tablets, as compared to those taking liquid formulation. These data suggest that the use of L‐T4 liquid formulation, as compared to that of tablets, resulted in a significantly higher number of DTC patients maintaining TSH values in range for the American Thyroid Association (ATA) risk score, reducing TSH variability over the time .…”
Section: Discussionmentioning
confidence: 94%
“…Three studies with 266 participants concerned comparison of liquid and tablet LT4 effectiveness of suppressive therapy in patients with DTC [30][31][32]. Two of them including 207 patients were prospective, randomised, and concluded that the use of LT4 liquid formulation, as compared to tablets, provided better control of TSH and resulted in a significantly higher number of DTC patients maintaining TSH values within range for the ATA risk score and reducing TSH variability over time [31,32]. Conversely, Giusti et al in a small study with 59 participants did not find any differences in TSH and thyroid hormone concentrations between the tablet and liquid L-T4 groups [30].…”
Section: Comparison Of the Effectiveness Of Liquid And Tablet Levothymentioning
confidence: 99%
“…Trzy badania poświęcono porównaniu skuteczności działania LT4 stosowanej w płynie lub w tabletkach w leczeniu supresyjnym 266 chorych na ZRT [30][31][32]. Dwa z nich, w których uczestniczyło 207 chorych, były randomizowanymi badaniami prospektywnymi.…”
Section: Porównanie Skuteczności Działania Lewotyroksyny W Postaci Płunclassified
“…Other reports showed better stabilization in the thyroid hormones profile with liquid thyroxine as opposed to tablet formulation. [35][36][37][38] In conclusion, the levothyroxine oral solution unit-dose ampules were bioequivalent to levothyroxine capsules within tightened confidence intervals when administered with or without water under fasting conditions. This new formulation may offer an additional treatment option for patients who have difficulty in swallowing solid dosage forms, potentially increasing patients' adherence to therapy.…”
Section: Discussionmentioning
confidence: 76%
“…It was also reported that oral liquid levothyroxine formulations could diminish the problem of levothyroxine malabsorption caused by lactose intolerance or Helicobacter pylori infection or bariatric surgery when using traditional tablet formulations. Other reports showed better stabilization in the thyroid hormones profile with liquid thyroxine as opposed to tablet formulation …”
Section: Discussionmentioning
confidence: 94%